Two-stage anaerobic digestion using protein-rich synthetic wastewater inoculated with anaerobic sludge - Syed Sabeer Ali, Sharifah Nazura; Omar, Rozita; Che Man, Hasfalina; Mohamad Idris, Aida Isma; Tajuddin, Hairul Anuar; Mahat, Siti Baizura; Abdullah, Luqman Chuah (Elsevier B.V., 2023)
Foam and scum have impacted digestion, causing process disturbances in several industries. The cause of foam and scum is difficult to determine as there are complex compounds in wastewater. Proteins are the primary compound found in food processing industries wastewater. This study investigates the effect of protein concentration on foaming and scum formation using protein-rich synthetic wastewater in a two-stage anaerobic digester inoculated with anaerobic sludge. The protein concentration in the digester was altered using gelatine as a protein source. The foaming tendency, scum production, biogas production, protein, and chemical oxygen demand (COD) removal, total volatile fatty acid (TVFA) concentration, and ammoniacal nitrogen (AN) concentration were measured to comprehend the findings. The results show no foaming and scum in the digester; however, sludge residue was present at high protein concentrations. The Fourier-transform infrared spectroscopy analysis revealed that the residue contained sludge and protein. The biogas production began to decrease at the protein concentration of 12 g/L. The TVFA and AN increased steadily with an increase in protein concentration in Tank 1, while the protein and COD removal percentage was higher in Tank 2.